2017
DOI: 10.4186/ej.2017.21.7.87
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Hierarchy Process for Stakeholder Participation in Integrated Water Resources Management

Abstract: Abstract. This paper focuses on the applying the Analytic Hierarchy Process (AHP) to Integrated Water Resource Management (IWRM) to develop a model for water resource management in the Pranburi watershed by using stakeholder participation. The hierarchy model structure of the Pranburi watershed was developed by the experts based on IWRM and classified into 4 criteria, 15 sub-criteria, and 3 alternatives. The questionnaire method was the tool used for obtaining a weighing for comparison between the pairs of cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The cognizant experiences of the experts showed that 84% have more than five years of experience in agricultural water management and rural development in Korea while 68% have more than five years of experience in governance. It has previously been reported that experts' opinions can help to classify and rank complex factors of water resources management [35]. Meanwhile, the expert with a minimum of five years of experience on a subject is considered to have adequate knowledge to offer an appropriate and relevant opinion.…”
Section: Analysis Of Delphi-ahp Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The cognizant experiences of the experts showed that 84% have more than five years of experience in agricultural water management and rural development in Korea while 68% have more than five years of experience in governance. It has previously been reported that experts' opinions can help to classify and rank complex factors of water resources management [35]. Meanwhile, the expert with a minimum of five years of experience on a subject is considered to have adequate knowledge to offer an appropriate and relevant opinion.…”
Section: Analysis Of Delphi-ahp Techniquementioning
confidence: 99%
“…The opinions of the experts were subjected to relative weights using pairwise comparisons based on the AHD method. This process can be regarded as a group decision-making process based on the analysis of individual expert rankings aimed at finding appropriate alternatives to the water resources problem [35]. The result of hierarchical analysis with experts' opinions evaluation based on the relative weight of criteria for the main components of agricultural water governance showed that core actors (0.316) should be the first priority when it comes to achieving the goal of water conservation and water-saving policy followed by law, policies, and systems (0.239), budget support (0.142), information sharing and communication (0.135), mutual learning (0.099), and external experts (0.069) (Table 4).…”
Section: Analysis Of Delphi-ahp Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…If the environment where the decision-making process takes place is fuzzy, then fuzzy numbers will be used for the evaluation concerning some deviations of the decision makers. According to the literature, the AHP method is a decision support tool that is widely employed to solve complex decision problems or as a weight-estimating technique in many fields such as water resource management, environmental management, economic development and medicine and healthcare [1,27,28,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This method is often used in research to improve drinking water supply as the research that was done by [16] Bojan Sradjevic and Medeiros in the year (2008). In Thailand year [18] (2015), Thungngern has done AHP approach and multicriteria decision analysis (MCDA) in water resources management. [9] Okeola (2012) did the same approach to evaluate the distribution of urban drinking water in Nigeria.…”
Section: Introductionmentioning
confidence: 99%